(untitled) (Comprehensive Journal of Science, 2025)
The Tunisian state went through several stages, but the immediate danger stemmed from both objective and strategic causes. The first was reflected in the weakness of the ruling sultans, the spread of corruption, the absence of effective reforms, the lack of credibility among the team running the country, thefts and embezzlement of treasury funds, and the crises plaguing the country, especially after the establishment of the International Financial Commission under French, British, and Italian supervision. The strategic reasons lie in the absence of a comprehensive vision for revitalizing the country’s borrowed debts, whether for water supply, railways, or other projects that, if properly invested, would yield ideal results for the country and its people. Thus, faced with a corrupt vision, corrupt management, and foreign ambitions, the country was plunged into a cumulative crisis with dire consequences.